2016
DOI: 10.3389/fmicb.2016.01839
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Ammonia Fiber Expansion Treated and Untreated Barley Straw in a Rumen Simulation Technique Using Rumen Inoculum from Cattle with Slow versus Fast Rate of Fiber Disappearance

Abstract: The purpose of this study was to determine the effect of rumen inoculum from heifers with fast vs. slow rate of in situ fiber digestion on the fermentation of complex versus easily digested fiber sources in the forms of untreated and Ammonia Fiber Expansion (AFEX) treated barley straw, respectively, using an artificial rumen simulation technique (Rusitec). In situ fiber digestion was measured in a previous study by incubating untreated barley straw in the rumen of 16 heifers fed a diet consisting of 700 g/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…The effect of a change from complex to easily digestible fibre sources (by means of chemical pretreatment) on the VFA production has been demonstrated by Griffith et al . (). They reported a similar decrease in acetate and acetate/propionate ratio, as well as an increase in propionate molar proportion.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of a change from complex to easily digestible fibre sources (by means of chemical pretreatment) on the VFA production has been demonstrated by Griffith et al . (). They reported a similar decrease in acetate and acetate/propionate ratio, as well as an increase in propionate molar proportion.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, AFEX treatment increased IVNDFD of corn stover and wheat straw by 19 to 20% (Bals et al, 2010). Recently, Griffith et al (2016) reported 35 and 27% greater in vitro dry matter digestibility (IVDMD) and IVNDFD due to AFEX treatment of barley straw. Feeding trials with lactating dairy cows using AFEX-treated rice straw have shown adequate intake and no adverse health effects with the treated material (Weimer et al, 2003;Blummel et al, 2014).…”
Section: Alkali Treatmentmentioning
confidence: 98%
“…An alternative to direct ammoniation alone that combines chemical and physical treatments is AFEX. The method involves ammoniating low-quality forages at high temperature and pressure, with subsequent pressure release and ammonia removal (Campbell et al, 2013;Griffith et al, 2016) or recycling. Bals et al (2010) observed 206% greater NDFD with AFEX treatment of late harvest switch grass relative to the untreated forage versus 56% greater digestibility with traditional ammoniation.…”
Section: Alkali Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Effluent was collected every day from days 6 to 8 in a 1.0-L container immersed in an ice water bath and filtered through a nylon cloth (Guangda Hengyi Co., Beijing, China) with an inner size of 8 cm × 12 cm and a pore size of 40 µm, as described in previous studies [15,31]. The residues were used to determine DM, organic matter (OM), NDF and CP as described in other studies [32,33], and filtrate was used to detect MPS.…”
Section: Samplingmentioning
confidence: 99%